2014
DOI: 10.1111/gcb.12657
|View full text |Cite
|
Sign up to set email alerts
|

Tree mineral nutrition is deteriorating in Europe

Abstract: The response of forest ecosystems to increased atmospheric CO2 is constrained by nutrient availability. It is thus crucial to account for nutrient limitation when studying the forest response to climate change. The objectives of this study were to describe the nutritional status of the main European tree species, to identify growth-limiting nutrients and to assess changes in tree nutrition during the past two decades. We analysed the foliar nutrition data collected during 1992-2009 on the intensive forest moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
239
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(266 citation statements)
references
References 57 publications
22
239
0
5
Order By: Relevance
“…Thereby the N/Mg ratio was thus consistently decreasing. Similar findings in regard to the temporal trends of N/K, N/Ca (an increase) and N/Mg (a decrease) ratios were reported by Jonard et al (2015) while the positive change in the foliar Mg concentration was more marked in plots with a low foliar Mg status. These trends of base cations are somewhat contradictory.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thereby the N/Mg ratio was thus consistently decreasing. Similar findings in regard to the temporal trends of N/K, N/Ca (an increase) and N/Mg (a decrease) ratios were reported by Jonard et al (2015) while the positive change in the foliar Mg concentration was more marked in plots with a low foliar Mg status. These trends of base cations are somewhat contradictory.…”
Section: Discussionsupporting
confidence: 86%
“…Phosphorus deficiency as a limiting factor in regard to the forest growth in the Bavarian Alps was reported by Mellert and Ewald (2014) regarding Norway spruce and by Ewald (2000) regarding European beech. Talkner et al (2014) documented a significant decrease of phosphorus nutrition throughout the beech stands in Europe which was also supported in other species by findings of Jonard et al (2015), who suggested the increased growth resulting from a high level of N deposition and from the global increase of atmospheric CO 2 as being the main driver behind the deterioration of mineral nutrition of trees. This conclusion can be supported by the significant increase of N/P ratio in both needle classes -though it is still within the optimal range (6-12) -indicating decreasing availability and possibly a nutritional imbalance of phosphorus in rela-tion to nitrogen uptake (Hüttl 1990;Drenowsky, Richards 2004;Luyssaert 2004;Ewald 2005).…”
Section: Discussionmentioning
confidence: 60%
“…The tendency towards less favourable foliage nutrition at plots with high N concentration in soil solution is in line with our second hypothesis that the exceedance of critical limits affects the nutritional status of trees. It remains to be investigated whether the temporal trends of mineral nutrition in foliage determined by Jonard et al (2015) could be explained by changes in N deposition or N concentrations in soil solution.…”
Section: Discussionmentioning
confidence: 99%
“…Even though many soils in central Europe are young, the P status of forests is often low or insufficient (Ilg et al, 2009;Jonard et al, 2015). Soil acidification and N eutrophication, intensified by anthropogenic deposits, additionally reduces plant available P (Mohren et 5 al., 1986).…”
Section: Introductionmentioning
confidence: 99%